Biohydrogen purification using metal hydride technologies. (14th December 2016) - Dunikov, D.; Borzenko, V.; Blinov, D.; Kazakov, A.; Lin, C.-Y.; Wu, S.-Y.; Chu, C.-Y.
Abstract: Metal hydrides are known for their ability of selective hydrogen absorption and might be used for hydrogen purification. We demonstrate separation of hydrogen/carbon dioxide mixtures with the use of two AB5 -type alloys. A metal hydride reactor was filled with 1 kg of "high-pressure" alloy La0.9 Ce0.1 Ni5 ( P eq = 1.96 bar at 293 K) and 1 kg of "low-pressure" alloy LaNi4.8 Mn0.3 Fe0.1 ( P eq = 0.38 bar at 293 K), maximum H2 capacity is 140 st.L, nominal operating H2 capacity is 110 st.L. Hydrogen concentration was in the range 40–60 vol.%, feed pressure 5.6 bar. Separation efficiency and hydrogen recovery depend on equilibrium pressure of absorption, which has to be as low as possible to increase hydrogen recovery. The purification rate of 81 st.L/h from a mixture containing 59 vol.% of hydrogen with recovery 94% was achieved for the "low-pressure" alloy. The results show that metal hydride H2 /CO2 separation unit can be a second stage of a biohydrogen upgrade system after a membrane module. Polymer membranes can defend metal hydrides from poisonous impurities and high selectivity of metal hydrides can improve the overall performance of the purification system. Highlights: Experiments on separation of H2 /CO2 mixtures with the use of two AB5-type alloys. Purification at 81 st.L/h from a H2 (59%)/CO2 (41%) mixture with recovery 94% was achieved at feed pressure 5.6 bar. Separation efficiency and hydrogen recovery depend on equilibrium pressure of absorption. Equilibrium pressure of absorption has to be lower than 0.5 bar to avoid preliminary compression of biohydrogen.